2008
DOI: 10.1111/j.1443-1661.2008.00819.x
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Pancreas Stenting Followed by Needle‐knife Fistulotomy in Patients With Sphincter of Oddi Dysfunction and Difficult Cannulation: New Method to Prevent Post‐ercp Pancreatitis

Abstract: In selected, high-risk, SOD patients, early, prophylactic pancreas stent insertion followed by needle-knife fistulotomy seems a safe and effective procedure with no or only minimal risk of post-ERCP pancreatitis. However, prospective, randomized studies are awaited to lend to support to our approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 31 publications
(61 reference statements)
0
14
0
2
Order By: Relevance
“…However, a stent might make biliary cannulation with a sphincterotome troublesome; a precut can be easier in these cases. Two studies suggested that a needle-knife biliary sphincterotomy over a pancreatic stent is safer than a conventional pull-type biliary sphincterotomy without a stent in patients with sphincter of Oddi dysfunction [27,28]. Multiple manipulations of the ampulla of Vater before pancreatic stenting or frequent contrast injections might be a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…However, a stent might make biliary cannulation with a sphincterotome troublesome; a precut can be easier in these cases. Two studies suggested that a needle-knife biliary sphincterotomy over a pancreatic stent is safer than a conventional pull-type biliary sphincterotomy without a stent in patients with sphincter of Oddi dysfunction [27,28]. Multiple manipulations of the ampulla of Vater before pancreatic stenting or frequent contrast injections might be a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, none of these has stood the test of time. Since 2003, the placement of small caliber (≤ 5 French gauge) plastic pancreatic duct stents was shown in multiple studies to be a reliable way for preventing severe (necrotizing) pancreatitis, if placed early in the procedure (ie, before significant instrumentation) [14,15]. A fascinating newcomer in the PEP pharmacoprophylaxis area is vardenafil, a phosphodiesterase type 5′-inhibitor, which is marketed for erectile dysfunction in men.…”
Section: Sod With An Intact Gallbladder?mentioning
confidence: 99%
“…Assuming successful application of the technique, standard wire-guided cannulation can be undertaken and the opening extended by standard sphincterotomy technique. Again, we recommend prophylactic pancreatic duct stenting when undertaking access papillotomy/ fistulotomy [17].…”
Section: Normal Anatomymentioning
confidence: 99%